2015
DOI: 10.1371/journal.pone.0140230
|View full text |Cite
|
Sign up to set email alerts
|

The (In)Effectiveness of Simulated Blur for Depth Perception in Naturalistic Images

Abstract: We examine depth perception in images of real scenes with naturalistic variation in pictorial depth cues, simulated dioptric blur and binocular disparity. Light field photographs of natural scenes were taken with a Lytro plenoptic camera that simultaneously captures images at up to 12 focal planes. When accommodation at any given plane was simulated, the corresponding defocus blur at other depth planes was extracted from the stack of focal plane images. Depth information from pictorial cues, relative blur and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…These different cues likely have different reliability across different regions of the visual field. For example, defocus blur is a more variable cue to depth than disparity near the fovea [46], but disparity is more variable than blur away from fixation [47]. Here, we have only shown that within a single cue, binocular disparity, depth information is integrated near-optimally across different regions of the visual field.…”
Section: Plos Computational Biologymentioning
confidence: 58%
“…These different cues likely have different reliability across different regions of the visual field. For example, defocus blur is a more variable cue to depth than disparity near the fovea [46], but disparity is more variable than blur away from fixation [47]. Here, we have only shown that within a single cue, binocular disparity, depth information is integrated near-optimally across different regions of the visual field.…”
Section: Plos Computational Biologymentioning
confidence: 58%
“…These different cues likely have different reliability across 124 different regions of the visual field. For example, defocus blur is a more variable cue to 125 depth than disparity near the fovea [29], but disparity is more variable than blur away 126 from fixation [30]. Here, we have only shown that within a single cue, binocular 127 disparity, depth information is integrated near-optimally across different regions of the 128 visual field.…”
mentioning
confidence: 67%
“…Similarly, Takeda, Iida and Fukui and Takeda and colleagues found mean accommodative differences of 0.68 D (for 4.00 D of accommodative stimulus) and even 0.77 D (for 3.00 D of accommodative stimulus) . In addition, rendered out‐of‐focus blur may enhance depth perception, with a potential effect also on accommodation.…”
mentioning
confidence: 87%